Recent advancement in the electrochemical performance of electrochemical capacitors based on biomass-derived porous carbon: A review - Ngidi, Nonjabulo P.D.; Koekemoer, Andrei F.; Ndlela, Siyabonga S. (Journal of energy storage, 2024)
The growth of the global population, coupled with higher levels of social and economic development has spurred technological advancement and industrialization. Consequently, there's a rising global energy demand, necessitating the pursuit of alternative energy sources for affordable implementation. In the last decade, extensive efforts focused on reducing fossil fuel use and exploring cost-effective, abundant, eco-friendly renewable energy sources such as wind, solar, and tidal energy. These sources are subject to daily and seasonal fluctuations. Thus, modular electrochemical capacitors (ECs) address their intermittency. The utilization of porous carbons in EC application has garnered significant attention due to their unique properties, low environmental impact, and ease of fabrication. Porous carbon materials possess a large surface area conductive to electrochemical reactions, enhancing charge storage and energy capabilities in ECs. Their porous structure enables rapid ion diffusion, which is crucial for rapid charge/discharge cycles and achieving high power density. Thus, ongoing developments aim to optimize cost and properties through various enhancements. Biomass-derived porous carbon (BDPC) has attracted intense attention because of its cost-effectiveness, sustainability, adjustable dimension, and superior electrical conductivity, making it a promising candidate for ECs. Furthermore, utilizing biogenic materials helps sequester CO2, contributing to renewable energy integration and reducing emissions from fuel conversion. This work reviews various synthesis approaches and applications of BDPC in ECs. Investigating related physicochemical properties of BDPC material, modification of nano-structural parameters, and developing appropriate strategies to enhance their functionality in EC is vital. This study also demonstrates that the electrochemical performance of BDPC is intricately influenced by a range of factors, including their pore structure, specific surface area, degree of graphitization, heteroatom doping, presence of a defect, and overall morphologies. [Display omitted] •Porous structure facilitates rapid ion diffusion for fast charge/discharge cycles.•Heteroatom-doping in porous carbon improve conductivity, and capacitance.•Higher conductivity allows faster charge transfer kinetics, enhancing power density.•Co-doping increases active sites for electrochemical reactions in porous carbon.